Efficiency, Specificity and Temperature Sensitivity of Cas9 and Cas12a RNPs for DNA-free Genome Editing in Plants - Banakar, Raviraj; Schubert, Mollie; Kurgan, Gavin; Rai, Krishan Mohan; Beaudoin, Sarah F.; Collingwood, Michael A.; Vakulskas, Christopher A.; Wang, Kan; Zhang, Feng (Frontiers in Genome Editing, 2022)
Delivery of genome editing reagents using CRISPR-Cas ribonucleoproteins (RNPs) transfection offers several advantages over plasmid DNA-based delivery methods, including reduced off-target editing effects, mitigation of random integration of non-native DNA fragments, independence of vector constructions, and less regulatory restrictions. Compared to the use in animal systems, RNP-mediated genome editing is still at the early development stage in plants. In this study, we established an efficient and simplified protoplast-based genome editing platform for CRISPR-Cas RNP delivery, and then evaluated the efficiency, specificity, and temperature sensitivity of six Cas9 and Cas12a proteins. Our results demonstrated that Cas9 and Cas12a RNP delivery resulted in genome editing frequencies (8.7 – 41.2%) at various temperature conditions, 22 °C, 26 °C to 37 °C, with no significant temperature sensitivity. LbCas12a often exhibited the highest activities, while AsCas12a demonstrated higher sequence specificity. The high activities of CRISPR-Cas RNPs at 22 °C and 26 °C, the temperature preferred by plant transformation and tissue culture, led to high mutagenesis efficiencies (34.0% to 85.2%) in the protoplast-regenerated calli and plants with the heritable mutants recovered in the next generation. This RNP delivery approach was further extended to pennycress (Thlaspi arvense), soybean (Glycine max) and Setaria viridis with up to 70.2% mutagenesis frequency. Together, this study sheds light on the choice of RNP reagents to achieve efficient transgene-free genome editing in plants.